Rethinking Gender and Epistemic Injustice: A Comparative Study of Male and Female Breast Cancer Memoirs - Mahua Bhattacharyya; Ajit K Mishra (Humanities)
Breast cancer patients’ experiences of epistemic injustice in healthcare is a well-established fact. However, the significant role that gender plays in deciding the nature of epistemic injustice encountered by male and female breast cancer patients is still underexplored. Through a comparative analysis of Alan F. Herbert’s The Pink Unicorns of Male Breast Cancer (2016) and Nina Riggs’ The Bright Hour: A Memoir of Living and Dying (2017), we explore how male and female breast cancer patients distinctly experience vitiated testimonial dynamics and hermeneutical marginalisation. Breast cancer patients can negotiate credibility deficit, identity crisis, and existential crisis caused by epistemic injustice through narrating. Taking from Fricker’s epistemic injustice, later contextualised in formal healthcare by Kidd and Carel, this study considers both the male and the female points of view to identify subtle instances of injustice and ways to overcome it. This article also articulates the need to overcome the stigma of considering breast cancer ‘a woman’s disease’ so that male breast cancer patients’ testimonies are equally prioritised along with female breast cancer patients. This comparative study highlights the ignorance inside institutional healthcare by foregrounding insensitivity toward all breast cancer patients and especially a lack of awareness of male breast cancer. Therefore, reading and writing such memoirs might secure future epistemic justice to all breast cancer patients irrespective of their gender.